2000
DOI: 10.1034/j.1600-0420.2000.078s230052.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Clinical Efficacy and Tolerance in Seasonal Allergic Conjunctivitis Management with 0.1% Olopatadine Hydrochloride versus 0.05% Ketotifen Fumarate

Abstract: ABSTRACT.Objective: To compare the clinical efficacy and tolerance of 0.1% olopatadine hydrochloride (OHC) versus 0.05% ketotifen fumarate (KF) in the management of allergic conjunctivitis. Materials and Methods: Eighty adult patients with a history of allergy (allergic conjunctivitis, hay fever, asthmatic bronchitis and dermatitis) that were showing allergic conjunctivitis signs and symptoms (itching, hyperemia, mucous discharge and tearing) at the time of inclusion in this study were evaluated. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 5 publications
1
33
1
1
Order By: Relevance
“…[20][21][22] According to aguilar et al olopatadine 0.1% shows superior efficacy in the rapid resolution of the signs and symptoms of allergic conjunctivitis. 23 Patient preference for olopatadine is also better compared to ketotifen. 24 In the CAC studies, olopatadine 0.1% twice daily was found to be more efficient than epinastine and loteprednol etabonate 0.2% in decreasing the signs and symptoms of allergic conjunctivitis such as itching, redness and chemosis.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] According to aguilar et al olopatadine 0.1% shows superior efficacy in the rapid resolution of the signs and symptoms of allergic conjunctivitis. 23 Patient preference for olopatadine is also better compared to ketotifen. 24 In the CAC studies, olopatadine 0.1% twice daily was found to be more efficient than epinastine and loteprednol etabonate 0.2% in decreasing the signs and symptoms of allergic conjunctivitis such as itching, redness and chemosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, SAC accounts for more than half of all ocular allergy cases, and many patients suffer ocular symptoms only, as did most patients in the present samples. 7,12,13 The present methodologic concerns would not normally arise in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Paracetamol and pseudoephedrine hydrochloride were allowed during the studies. Clinic visits were scheduled for days 0 (randomization and start of study treatment), 3,7,14,30, and 42 (last day of treatment). A final visit followed 2 to 3 days later.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a study from the United Kingdom 4 found that patients using olopatadine made fewer visits to their general practitioner than patients using cromolyn, resulting in lower overall cost of healthcare. Results of studies of patient preferences and effi cacy of olopatadine 0.1% (twicedaily preparation) vs ketotifen 0.025% are mixed, [5][6][7][8] and no study has compared olopatadine 0.2% (once-daily preparation) with overthe-counter ketotifen.…”
Section: Allergic Conjunctivitismentioning
confidence: 99%